2020
DOI: 10.1001/jamaoto.2019.3622
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Pediatric Dysphagia

Abstract: ppropriate nutritional intake is essential for the rapid growth and development that occurs during infancy and childhood. 1 Feeding and swallowing dysfunction are diagnosed with increasing frequency, especially in children with a history of prematurity, neuromuscular disorders, cardiopulmonary disorders, anatomic anomalies of the upper aerodigestive tract, and gastrointestinal tract disorders. [2][3][4] Early diagnosis and intervention by a multidisciplinary team are essential to the management of swallowing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 79 publications
0
72
0
9
Order By: Relevance
“…Despite dysphagia was reported in healthy children, it is more common in pediatric patients with a history of prematurity, neuromuscular disorders, cardiopulmonary disorders, upper aero-digestive tract congenital anomalies, and gastrointestinal tract disorders [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite dysphagia was reported in healthy children, it is more common in pediatric patients with a history of prematurity, neuromuscular disorders, cardiopulmonary disorders, upper aero-digestive tract congenital anomalies, and gastrointestinal tract disorders [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These are associated with delays in sensation and motor control. 8 In both children there were no other significant neurodevelopment concerns at the time of their diagnosis with these injuries. They had continued dysphagia as far as 2 years of life despite normal speech development.…”
Section: Discussionmentioning
confidence: 83%
“…Dysphagia is defined as difficult or abnormal swallowing. 1 A US national health survey conducted in 2012 found that among 61 million children about 1% suffered a swallowing problem lasting greater than 1 week in the previous year. 2 Dysphagia is prevalent in specific populations, including premature infants, and children with cerebral palsy, traumatic brain injury, craniofacial abnormalities, and children with medical complexity.…”
Section: Introductionmentioning
confidence: 99%